Control of Emission Color of High Quantum Yield CH3NH3PbBr3 Perovskite Quantum Dots by Precipitation Temperature. Issue 9 (14th July 2015) - Huang, He; Susha, Andrei S.; Kershaw, Stephen V.; Hung, Tak Fu; Rogach, Andrey L.
<x xml:space="preserve">Abstract</x> Emission color controlled, high quantum yield CH3NH3PbBr3 perovskite quantum dots are obtained by changing the temperature of a bad solvent during synthesis. The products for temperatures between 0 and 60 °C have good spectral purity with narrow emission line widths of 28–36 nm, high absolute emission quantum yields of 74% to 93%, and short radiative lifetimes of 13–27 ns.